Effects of channel surface finish on blood flow in microfluidic devices - Prentner, S.; Allen, David M.; Larcombe, L. D.; Marson, Silvia; Jenkins, Karl W.; Saumer, M. (Springer, 2010)
The behaviour of blood flow in relation to microchannel surface roughness has been investigated. Special attention was focused on the techniques used to fabricate the microchannels and on the apparent viscosity of the blood as it flowed through these microchannels. For the experimental comparison of smooth and rough surface channels, each channel was designed to be 10mm long and rectangular in cross-section with aspect ratios of â ¥100:1 for channel heights of 50 and 100Î¼m. Polycarbonate was used as the material for the device construction. The shims, which created the heights of the channels, were made of polyethylene terephthalate. Surface roughnesses of the channels were varied from Rz of 60nm to 1.8Î¼m. Whole horse blood and filtered water were used as the test fluids and differential pressures ranged from 200 to 5000Pa. The defibrinated horse blood was treated further to prevent coagulation. The results indicate that a surface roughness above an unknown value lowers the apparent viscosity of blood dramatically due to boundary effects. Furthermore, the roughness seemed to influence both water and whole blood almost equally. A set of design rules for channel fabrication is also presented in accordance with the experiments performed.
Keywords: Blood; Viscosity; Microchannel; Roughness